SUBMARINE LANDSLIDE AND LOCALIZED TSUNAMI POTENTIALITY OF MENTAWAI BASIN, SUMATRA, INDONESIA - Haryadi Permana; C. Singh (Marine Geological Institute of Indonesia, 2008)
The new bathymetry and seismic data were acquired during the PreTI-Gap marine survey (February 15 to March 6, 2008). The survey was carried out along the NE margin of Mentawai Island using multi-beam swath bathymetry equipment, and 28-channels seismic streamer and four-airgun source. The first target was the Mega Island region near the epicenter of the 2007 great earthquake. The shallow bathymetry is characterized as a flat coral platform suggesting that 200 km elongated plateau is slowly subsiding without any active faults. Further north, from South Pagai to North of Siberut Islands, the seafloor morphology changes significantly. The deep and wide canyons or valleys produce very rough seafloor morphology between 50 and 1100 m water. In general, the submarine topography shows two break slopes at different depths. Between slope breaks, the undulating, hilly and circular features dominate, possibly caused by landslides. A push-up ridge is observed that dams the sediments eroded within a steep slope northeastward side. The seismic reflection data acquired along 14 dip seismic lines at the NE flank of Mentawai Islands, from Siberut to the South of Pagai Islands. We observed a set of southwestward dipping back thrust bounding the NE margin of the Mentawai Island. Keywords: submarine landslide, tsunami, Mentawai basin, Sumatra. Data batimetri dan seismik baru telah dihasilkan selama survey kelautan PreTi-Gap (15 Februari hingga 6 Maret 2008). Survei dilaksanakan sepanjang tepian timurlaut P. Mentawai menggunakan peralatan multibeam, seismic saluran ganda 28 kanal dengan sumber energi airgun. Sasaran pertama adalah memetakan kawasan pulau dekat pusat gempa tahun 2007. Kenampakan batimetri dangkal dicirikan dengan adanya dataran terumbu karang yang secara perlahan mengalami penurunan tanpa aktifitas sesar. Lebih jauh ke Utar, dari Pagai Selatan ke utara P. Siberut, morfologi dasar laut memperlihatkan perubahan secara signifikan, dimana lembah dasar laut memiliki lebar dan beda kedalaman antara 50 hingga 1100 meter. Secara umum, topografi dasar laut memperlihatkan dua kemiringan pada kedalaman yang berbeda dengan dicirikan adanya kenampakan perlipatan, perbukitan dan bentuk yang melingkar diperkirakan sebagai hasil gelinciran. Sebanyak 14 line data seismik refleksi pada sayap bagian timurlaut P. Mentawai, dari Siberut hingga ke selatan P. Pagai memperlihatkan adanya bukti sesar naik yang miring ke arah baratdaya yang masih satu set dengan tepian timurlaut P. Mentawai. Kata kunci: longsoran bawah laut, tsunami, Cekungan Mentawai, Sumatra.